AGAMA DAN PERUBAHAN SOSIAL EKONOMI - Nanang Rustandi (Tsaqofah, 2020)
Research on religion and socio-economic changes in the community around the Gunung Padang site, Karyamukti Village, Campaka District, Cianjur Regency originated from the emergence of a local community in carrying out its religion and culture in the form of socio-economic changes. The focus of the research reveals how religious the people around the Gunung Padang site are. How is the socio-economic culture of the community around Mount Padang with the Gunung Padang site, as well as how the religious and socio-economic changes of the community after the restoration (excapation) of the Gunung Padang site. This study uses a qualitative research method, to analyze the religious relationship between the community and the socio-economic culture of the community around ancient sites using a phenomenological approach. The results of this study indicate that the religion of the people around the site is greatly influenced by the process of combining religious understanding and local culture that has been hereditary. The form is through religious expressions, namely belief (theology), ritual (rites) and community (community).